Spatial Variation and Community Structure of Trichoptera Larvae as a Basis for Biomonitoring in the Bone River, Gorontalo - Miftahul Khair Kadim; Nuralim Pasisingi; Abdul Hafidz Olii (Biosel Biology Science and Education, 2026)
This study aimed to examine the community structure of Trichoptera larvae in the Bone River, Gorontalo (Indonesia), by evaluating family-level composition, dominance patterns, and spatial variation across five sampling stations (St.1-St.5). Trichoptera larvae were collected using standardized sampling methods, identified to the family level, and analyzed using multiple diversity metrics, including the Shannon, Simpson, Evenness, and Margalef indices. Differences in taxon richness among stations were assessed using rarefaction analysis, while community structure patterns were further explored using multivariate approaches based on Bray–Curtis dissimilarity, non-metric multidimensional scaling (NMDS), and hierarchical cluster analysis. A total of 754 individuals representing eight families were identified. Hydropsychidae strongly dominated the community, accounting for more than 70% of the total individuals. Diversity indices revealed spatial variation in community balance, with Station 5 exhibiting the highest diversity and evenness values, indicating a relatively more balanced community structure. Rarefaction analysis suggested that differences in richness were not solely driven by sampling effort. Multivariate analyses based on Bray-Curtis dissimilarity, hierarchical clustering, and NMDS demonstrated spatial differentiation in community composition along the river gradient, largely associated with variations in family dominance. Water quality parameters (temperature, pH, and dissolved oxygen) were within national quality standards, indicating conditions generally supportive of aquatic life. The observed variation in community structure therefore likely reflects local habitat dynamics rather than broad physicochemical stress. This study provides baseline data on Trichoptera communities in the Bone River and highlights the ecological importance of Hydropsychidae in shaping community structure, supporting the potential application of Trichoptera as biomonitoring indicators in riverine ecosystems.  Keywords: Trichoptera, River, Community Structure, Spatial Variation, Biomonitoring